Teoria do funcional da densidade acoplada ao modelo de Hubbard de uma banda aplicada ao supercondutor La2−xSrxCuO4 - Gonzalez, Uger Alfonso Herrera (2020)
In this work we present the results of a methodology that combines first-principle Density Functional Theory calculations with the Green’s functions method in order to treat strongly correlated electronic systems. The material system selected for this study was the La2CuO4. Taking into account that superconductivity in cuprates occurs mainly at the CuO2 planes, only the electronic bands at these planes have been considered. Firstly the electronic levels were calculated in a dense grid of points on the CuO2 planes through the Density Functional Theory. We then used the Green’s functions method, within the one-band Hubbard model with repulsive interaction to include the electronic correlation. The correlated bands were calculated for an occupation number of nT = 0.85 and different values of the Coulomb interaction U . Further, the correlated bands were also obtained for a U value of 1.6 eV, and various occupation numbers nT . The following quantities have also been calculated: density of states, spectral function, specific heat, and chemical potential. The specific heat, as a function of temperature, showed a two-peak structure: one associated to spin fluctuations at low temperatures, and another associated to charge fluctuations, for higher temperatures. The maximum of the chemical potential was showed to depend on the Coulomb interaction U . These results were compared with those obtained using the Tight-Binding method in a square lattice, instead of the first principles Density Functional Theory calculations. It results from this comparison that this methodology can be also applied to other strongly correlated systems.